Prevalence and cost of hospitalized patients with asymptomatic COVID-19 in 2020 in Spain - Álvarez-del Río, Blanca; Sánchez-de Prada, Laura; Álvaro-Meca, Alejandro; Martín-Fernández, Marta; Álvarez, F. Javier; Tamayo, Eduardo; Gutiérrez-Abejón, Eduardo (Frontiers in Public Health, 2023)
Introduction COVID-19 transmission has been characterized by the presence of asymptomatic patients. Additionally, most studies evaluating costs focus on symptomatic COVID-19 cases. Objective To describe the prevalence, characteristics, and costs of asymptomatic COVID-19 cases at admission in Spanish hospitals in 2020. Methods A nationwide study was performed, and data of hospitalized patients were collected of the Minimum Basic Data Set in Spain during 2020. Patients with COVID-19 codes as a primary and as a secondary diagnosis at admission were selected. Variables collected included age, sex, length of stay, in-hospital death, admission, length of stay and death in intensive care unit, mechanical ventilation and ventilatory assistance. COVID-19 related hospital costs were calculated using diagnosis-related groups from the Minimum Basic Data Set. Patients and costs were disaggregated by sex, age group, intensive care unit admission and epidemic wave (first or second) and main diagnosis. Results A total of 14,742 patients were admitted with asymptomatic COVID-19 in Spanish hospitals representing 6.35% of all COVID-19 admitted patients. The total cost of admissions with asymptomatic COVID-19 was €105,933,677.6 with a mean cost per patient of €7,185.8 with higher mean cost in the first wave despite only 2.7% of cases were found during that time. Based on primary diagnosis, the higher number of cases of asymptomatic COVID-19 were found in “Pregnancy, childbirth and the puerperium” followed by “diseases of the circulatory system”. Conclusions There was a high prevalence of asymptomatic cases during screening at admission process in Spanish hospitals in 2020. The highest number of cases was found among the group of “pregnancy, childbirth, and puerperium” followed by “diseases of the circulatory system.” The higher costs might be due not only to the main pathology at admission but to the associated healthcare provisions needed in case of positive COVID-19 testing.